Pajubá: linguagem da comunidade LGBTI+ como repertório artístico, social e cultural - Rodrigues, Paulo Ricardo Aires (Universidade Federal do Tocantins, 2023)
The purpose of this article is the result of two scientific initiation research PIBITI /CNPq (2021-2022) and PIBIC /CNPq (2020-2021). The research had the following objectives: i. identify the beliefs and attitudes of the LGBTI+ group that uses the Pajubá language in certain social spaces in Palmas; ii. Define the linguistic status of Pajubá: dialect, slang, group language; iii. Know and catalog the belonging and self-identified Pajubávocabulary among the LGBTI+ community of Palmas-TO. For this study, an activity resulting from the TCC Course Completion Work, the proposal is to develop the creation of an artistic scene (soliloquy) from the results obtained in previous research. The idea is to reframe and transform some of the entries (words and/or expressions) of the pajubá into an artistic scene which will be presented at Sala Aberta, edition 2023-01 that will take place between July 3rd and 7th, 2023, at the Palmas Campus. - UFT. It is hoped that this work can help those belonging to the LGBTI+ community in social recognition, guaranteeing them their basic rights to coexist within society, respecting their language and their ways of living and acting